Iron-modified biochar improves plant physiology, soil nutritional status and mitigates Pb and Cd-hazard in wheat (Triticum aestivum L.) - Algethami, Jari S.; Irshad, Muhammad Kashif; Javed, Wasim; Alhamami, Mohsen A. M.; Ibrahim, Muhammad (Frontiers in Plant Science, 2023)
Environmental quality and food safety is threatened by contamination of lead (Pb) and cadmium (Cd) heavy metals in agricultural soils. Therefore, it is necessary to develop effective techniques for remediation of such soils. In this study, we prepared iron-modified biochar (Fe-BC) which combines the unique characteristics of pristine biochar (BC) and iron. The current study investigated the effect of pristine and iron modified biochar (Fe-BC) on the nutritional values of soil and on the reduction of Pb and Cd toxicity in wheat plants (Triticum aestivum L.). The findings of present study exhibited that 2% Fe-BC treatments significantly increased the dry weights of roots, shoots, husk and grains by 148.2, 53.2, 64.2 and 148%, respectively compared to control plants. The 2% Fe-BC treatment also enhanced photosynthesis rate, transpiration rate, stomatal conductance, intercellular CO2, chlorophyll a and b contents, by 43.2, 88.4, 24.9, 32.5, 21.4, and 26.7%, respectively. Moreover, 2% Fe-BC treatment suppressed the oxidative stress in wheat plants by increasing superoxide dismutase (SOD) and catalase (CAT) by 62.4 and 69.2%, respectively. The results showed that 2% Fe-BC treatment significantly lowered Cd levels in wheat roots, shoots, husk, and grains by 23.7, 44.5, 33.2, and 76.3%. Whereas, Pb concentrations in wheat roots, shoots, husk, and grains decreased by 46.4, 49.4, 53.6, and 68.3%, respectively. Post-harvest soil analysis showed that soil treatment with 2% Fe-BC increased soil urease, CAT and acid phosphatase enzyme activities by 48.4, 74.4 and 117.3%, respectively. Similarly, 2% Fe-BC treatment significantly improved nutrients availability in the soil as the available N, P, K, and Fe contents increased by 22, 25, 7.3, and 13.3%, respectively. Fe-BC is a viable solution for the remediation of hazardous Cd and Pb contaminated soils, and improvement of soil fertility status.